2017
DOI: 10.1038/modpathol.2016.236
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumor of soft tissue is genetically distinct from its bone counterpart

Abstract: Giant cell tumors of bone are locally aggressive bone neoplasms with a predilection for young adults. Histologically, they are composed of histiocytoid to spindled mononuclear cells, admixed with numerous large osteoclastic giant cells. Giant cell tumors of soft tissue are rare tumors that bear striking histological resemblance to giant cell tumors of bone and might be regarded as a soft tissue analog thereof. Point mutations of the H3F3A gene (coding for a histone H3.3 protein) at the Gly34 codon, mostly G34W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 25 publications
1
32
1
Order By: Relevance
“…In the present series, although we confirm that GCT‐B predominantly has H3F3A mutations at glycine 35, with no involvement of H3F3B , we show that GCT‐ST does not have this molecular alteration. These results are in keeping with a recent analysis of 15 GCT‐STs, in which no somatic mutation was detected in H3F3A , H3F3B , H3F3C , HIST2H3A , HIST2H3C , and HIST2H3D . In addition, our results were confirmed by COLD PCR analysis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present series, although we confirm that GCT‐B predominantly has H3F3A mutations at glycine 35, with no involvement of H3F3B , we show that GCT‐ST does not have this molecular alteration. These results are in keeping with a recent analysis of 15 GCT‐STs, in which no somatic mutation was detected in H3F3A , H3F3B , H3F3C , HIST2H3A , HIST2H3C , and HIST2H3D . In addition, our results were confirmed by COLD PCR analysis.…”
Section: Discussionsupporting
confidence: 93%
“…In a recent study, no H3F3 mutations were detected in a series of 15 GCT‐STs, indicating that GCT‐ST might be genetically different from its osseous counterpart . To expand these observations, we compared a series of GCT‐STs and GCT‐Bs with regard to the presence of H3F3A and H3F3B mutations and several immunophenotypic markers.…”
Section: Introductionmentioning
confidence: 98%
“…The neoplastic mononuclear cells of GCT-ST display a similar immunophenotype as their osseous counterparts. They express monocyte-macrophageassociated antigen CD68, tartrate-resistant acid phosphatase, and smooth muscle actin, but not CD45, desmin, S100 protein, and lysozyme [16][17][18][19][20]. The osteoclastic giant cells express CD68, but not CD163 [28].…”
Section: Discussionmentioning
confidence: 99%
“…GCT-ST is considered a tumor of low malignant potential, but giant cell tumor of bone is a locally aggressive tumor. Lee et al suggested the genetic distinction between GCT-ST and giant cell tumor of bone [ 16 ]. They analyzed the genotype of H3F3A in 15 cases of GCT-ST.…”
Section: Discussionmentioning
confidence: 99%